Profile of Pneumocystis JiroveciiPneumoia in HIV/AIDS Patients in Dr. Soetomo General Hospital of East Java Province - Pius Sebastian Ginting; Bramantono; RestiYudhawati Meliana; Musofa Rusli (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Human immunodeficiency virus (HIV)-infected patients if not treated will experienceacquired immunodeficiency syndrome (AIDS). People with AIDS will suffer opportunistic infection.One of the common opportunistic infections is Pneumocystis jirovecii pneumonia (PCP). PCP is aninfection caused by the fungus Pneumocystis jirovecii which infects patient’s lungs. The purpose of thisstudy is to analyze the profile of HIV/AIDS patients with PCP in Dr. Soetomo Hospital.Methods: This is a retrospective descriptive study based on medical records obtained from the inpatientward of Dr. Soetomo General Hospital Surabaya. A total 21 patients enrolled in this study who met theinclusion criteria. The data are retrospectively described by demographic characteristics, CD4 count,clinical symptoms, blood gas, and lungs radiographic features.Conclusion:Major findings of PCP in HIV/AIDS patients was in the group of age 25-49 years (85,7%),male (85,7%), high school graduate (71,4%), employed and unmarried (66,7%). The most commonclinical symptoms were dyspnea (100%), PaO2 ≥70 mmHg (61,97%), CD4 count <50 cells/μL (76,2%)and the most common radiographic features was bilateral interstitial infiltrates (95,2%).